The Skilled Helper A Problem-Management and Opportunity-Development Approach to Helping - Egan, Gerard (Pacific Grove, Calif. : Brooks/Cole/Thomson Learning, 2002)
Using a practical, three-stage model that drives client problem-managing and opportunity-developing action, Gerard Egan helps the reader master the steps of a helping model, building competence and confidence as a helper along the way.
Previous ed.: 1998.
Ill. on lining paper.
Includes bibliographical references (p. 369-391) and index.
Keywords: Counseling; Helping behavior; Psychology